Composing music for puisi Melayu: exploring the music composition of 'Prosa Air Mata' - Mohamed Razali, Camellia Siti Maya; Salleh, Marzelan (Universiti Putra Malaysia Press, 2019)
The aesthetic science of human ecology constantly attempts to find the perfect balance of the current dynamic human environment. In the quest for balance, contemporary ideas have taken over traditional thoughts and identity issues arise in the community, for example in the arts. The art of music and puisi Melayu (Malay poetry) have always strived on the quest for aesthetical beauty. Therefore, the intent of composing music for 'Prosa Air Mata', a poetry written by Dato' Usman Awang, is justifiably appropriate. The combination of two different art forms - music and poetry - into a single artwork embodies the creativity and emotive qualities of music and text. Responding towards the issues of identity, the prominence of a Malay theme, especially in the choice of a Malay language source of text, is juxtaposed with a contemporary music ensemble not found in Malay culture. The resulting vocal composition of 'Prosa Air Mata' shows the composer highlighting Malay literature into a more contemporary idiom of music and arts.